INCIDENCE OF POSTURAL CHANGES AND TEMPOROMANDIBULAR DISORDERS IN STUDENTS - Chaves, Paulo de Jesus (Acta Ortop Bras, 2017)
OBJECTIVE: The aim of this study was to identify the incidence of postural changes and temporomandibular disorders (TMD) in children and adolescents . METHODS: We selected 117 individuals aged 10-18 years from a state school in the Zona da Mata region of Minas Gerais. The students were evaluated in four stages: assessment of body weight and height and calculation of body mass index; posture evaluation using a questionnaire developed by the researchers; application of a questionnaire recommended by the American Academy of Orofacial Pain to assess TMD; and, finally, application of the Fonseca anamnesis questionnaire . RESULTS: Of our sample, 26.36% had no TMD, 50.9% had mild TMD, 21.8% moderate TMD, and 0.9% severe TMD. Of the participants with moderate or severe TMD (30.8%), about 56% had some kind of change in head positioning. We found that 88% of the children with moderate or severe TMD had changes in the shoulders . CONCLUSION: The postural changes found in the head and shoulders are related to the biomechanical adaptation of the muscles of mastication and consequent changes in the TMJ. Level Of Evidence Iii, Non-Consecutive Patient Study Without Gold Reference Standard Applied Uniformly.